Body size is a good proxy for vertebrate charisma. (November 2020) - Berti, Emilio; Monsarrat, Sophie; Munk, Michael; Jarvie, Scott; Svenning, Jens-Christian
Abstract: The charisma of species, i.e., their popularity among people, influences how much we are willing to invest in seeing, studying, and protecting them. Previous studies have investigated the drivers of animal charisma, but because collection of species popularity data is costly in terms of time and resources, these are often restricted to a small number of species, making it difficult to generalize results at a scale useful for macroecological studies. Here, we test the hypothesis that animal charisma scales with species body size using nine open-access datasets on animal charisma for 13, 680 species from four vertebrate classes: amphibians, birds, mammals, and reptiles. We performed linear mixed models using all studies taken together and, in supplement, linear models on each study separately. We found that animal charisma scales positively with species body size across different vertebrate classes, geographic areas, and charisma estimation methodologies. This general scaling relationship between body size and animal charisma supports large-bodied species to have disproportionate importance for conservation due to their high appeal on people. These findings suggest that body size can be used as a proxy for the charisma of species at broad spatial scales and for large numbers of species, as an alternative to more resource-intensive surveys. Highlights: Larger species are in general more charismatic than smaller ones and inspire strong positive responses in people Visibility and concurrence with humans also determine species charisma Extremely small species often have higher charisma than expected by body size alone The scaling of species charisma with body size can be used to identify highly charismatic species in large-scale assessments Large-bodied species have disproportionate importance for conservation due to their high appeal on people